Current trends and future research themes for sustainable business management post-COVID-19. (10th October 2022) - Ozkan-Ozen, Yesim Deniz; Ozbiltekin-Pala, Melisa
Recently, it became more important for businesses to remain dynamic in both macro and micro environmental conditions to ensure operations are sustainable. The new sustainable business approaches and management practices that emerged during the COVID-19 era have increased business' resilience to social, environmental, and financial problems. Sustainable business management requires knowledge about relevant research in sustainable business management, regarding both the COVID-19 era and future trends. Therefore, this study used a systematic literature review to identify future research themes related to sustainable business management in the post-COVID-19 era. Based on an analysis of current research tendencies related to the COVID-19 pandemic and sustainable business management practices, six research themes were proposed for integrated studies in manufacturing and service industries. These findings contribute to the current literature by providing a new perspective on research into sustainable business management in the post-COVID-19 era.